2014
DOI: 10.1016/j.indcrop.2014.06.055
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study on coagulant performance and floc characterization of natural Cassia obtusifolia seed gum in treatment of raw pulp and paper mill effluent

Abstract: showed that flocs formed using C. obtusifolia gum was highly fibrous-like and aggregate, 31 whereas irregularly-shaped and aggregate for alum. In conclusion, C. obtusifolia gum could be 32 served as a promising alternative to alum as a natural coagulant in treatment of PPME.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(60 citation statements)
references
References 44 publications
3
55
1
1
Order By: Relevance
“…Similarly, for the response variables, turbidity and COD, removals of 98.1 % and 75.4 % were obtained respectively. These results are higher to those reported by Bhuptawat et al [23] and Subramonian et al [20], who found COD removals of 50 % and 36.2 % for the natural coagulants Moringa oleifera and Cassia obtusifolia, respectively. In addition, we found that the BOD decreased from 323 mg/l in the untreated wastewater to 91 mg/l in the wastewater treated with thermal water, obtaining a 71.8 % removal.…”
Section: Figcontrasting
confidence: 69%
“…Similarly, for the response variables, turbidity and COD, removals of 98.1 % and 75.4 % were obtained respectively. These results are higher to those reported by Bhuptawat et al [23] and Subramonian et al [20], who found COD removals of 50 % and 36.2 % for the natural coagulants Moringa oleifera and Cassia obtusifolia, respectively. In addition, we found that the BOD decreased from 323 mg/l in the untreated wastewater to 91 mg/l in the wastewater treated with thermal water, obtaining a 71.8 % removal.…”
Section: Figcontrasting
confidence: 69%
“…Several studies have demonstrated the effective removal of turbidity in different types of water, with the application of natural coagulants obtained from basil, Senna, Moringa and Bean seeds; Cactus, rubber, and bark mucilage; and Acacia and Campano wood, among other plants and potential sources [4,5,8,9,13,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…For the Sinú river raw water turbidity, which is until 100 NTU, it was possible a maximum coagulant activity for both extracts of 40 %. However, when the raw water initial turbidity was higher than 150 NTU the coagulant activity increased in a 80%, in a proportional way with the increase of the applied doses, in particular, with the gummy exudate of Campano, giving as a result flocs with gummy appearance that were formed from the extract own characteristics [9]. For both extracts, dosages higher than 60 mg/L did not have a significative coagulant activity on the samples, even that, they altered the initial physicochemical characteristics, as the increase of residual turbidity and color.…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, the protein content was determined by the Biuret method (absorbance at λ= 540 nm) using a standard albumin solution from bovine serum (ABS, 30%±2% in NaCl 0.85%, SIGMA-ALDRICH, A7284, 50ml, Lot # SLBD0064V), the colorimetric measurements were made with a spectrophotometer Thermo Scientific Genesys 10S UV-Vis; also an analysis by Fourier Transform Infrared Spectrometry -FTIR using a Shimadzu IRTracer-100 was performed in order to identify the active functional groups of molecules involved in the coagulant process [9].…”
Section: Collection and Selection Of Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation